Validation of Strategic Memory Advanced Reasoning Training as an efficient and effective approach to treating warfighters with persistent cognitive complaints associated with mild traumatic brain injury - Darr, Andrew J.; Basham, Angela; Ryan, Jessica L.; Caswell, Melissa; Lopez, Juan; Zientz, Jennifer; Venza, Erin; Babakhanyan, Ida; Chapman, Sandra; Bailie, Jason M. (Frontiers in Neurology, 2025)
IntroductionThis study directly compared the relative effectiveness of Strategic Memory Advanced Reasoning Training (SMART), which focuses on metacognitive strategies, to a traditional cognitive rehabilitation (CR) program previously developed and validated for the Study of Cognitive Rehabilitation Effectiveness study (SCORE), in treating warfighters with a history of mild traumatic brain injury (mTBI) and persistent post-concussive symptoms (PCS).MethodsA total of 148 active-duty service members (SMs) were recruited for this randomized controlled trial (RCT). Participants were randomly assigned to either the SMART (n = 80) or SCORE (n = 68) intervention arms. Outcome measures were administered at the start (T1) and end of treatment (T2), and at 3 months post-treatment (T3). Only participants with data from all timepoints and adequate performance validity (SMART: n = 51; SCORE: n = 43) were used in analyses. The primary outcome measure was the Global Deficit Scale (GDS), a composite of seven different objective measures of cognitive performance. Secondarily, participants completed the Neurobehavioral Symptom Inventory (NSI) and Key Behaviors Change Inventory (KBCI) self-report measures of post concussive symptoms (PCS). Lastly, a cost effectiveness analysis (CEA) was performed directly comparing the relative efficiencies of the two CR interventions.ResultsMixed Analysis of Variance (ANOVA) showed a significant decrease in GDS scores from T1 to T3 (p < 0.001, ηp2 = 0.217), irrespective of intervention type (p = 0.986, ηp2 = 0.000). The greatest improvement occurred between T1 (SMART: M = 0.70, SD = 0.79; SCORE: M = 0.70, SD = 0.72) and T2 (SMART: M = 0.29, SD = 0.58; SCORE: M = 0.29, SD = 0.40), with scores plateauing at T3 (SMART: M = 0.28, SD = 0.52; SCORE: M = 0.29, SD = 0.57). Similarly, there was a significant decrease in NSI scores over the same period (p < 0.001, ηp2 = 0.138), regardless of intervention type (p = 0.412, ηp2 = 0.010). Additionally, treatment improved patient perceived functionality (KBCI) from T1 to T2 and these gains remained stable at T3 (p < 0.001, ηp2 = 0.377). CEA revealed SMART represented a 60% reduction in cost compared to SCORE.DiscussionThis study demonstrates that SMART is an effective strategy for reducing cognitive deficits and PCS in SMs with a history of mTBI, producing comparable outcomes to a traditional CR program in less time and with improved cost efficiencies.